Effect of Ag addition on mechanical properties of zinc-based alloy - Md. Azizan, Farihan; Purwanto, Hadi; Adesta, Erry Yulian Triblas; Mustafa, Mohd. Yusry (2011)
The application of Zinc-based alloy in giftware industry instead of tin is interesting since its price is less expensive. However, the use of zinc has some limitations such as mechanical properties. Machining, rolling and soldering are the most common manufacturing process in giftware. Therefore, modifying the properties of zinc based alloy is needed to use it for giftware material. This work focused on improving the mechanical properties of Zn based alloy by adding Ag. Mechanical properties were studied based on its tensile strength and elongation. The samples were prepared by melting the zinc at desired temperature then the alloying elements were added before poured into a mold to produce tensile test specimens. Fractography of the tensile specimen was further observed by using Scanning Electron Microscope (SEM) and Optical Microscope. The results showed that addition of Ag has significant effect on the improving of tensile strength and elongation of the zinc based alloy. The fracture surface of the tensile test specimen showed a mixed mode of fracture exhibiting ductile failure and brittle failure. Alloy with higher content of Ag tends to have more ductile failure then the brittle one. The alloys of Zn-20Sn-0.5Ag have very good tensile strength and elongation, which are better than Zn-20Sn-0.03Ag and Zn-20Sn-0.27Ag alloys.